Iron Oxide Colloid Mobility as Affected by Solid Matrix Wetting Properties - Carstens, J.F. (2020)
Flow column results elucidated that decreasing sand wettability had no relevant effect on OMCG colloid mobility. In contrast, colloid retention increased with ionic strength in each type of sand packing. Classic DLVO interactions could predict trends in colloid retention by the respective characteristics of energy barriers and secondary minima. The extension with Lewis acid–base interactions in the XDLVO approach led to the prediction of significant short‐range (∼2 nm) attractive interaction energies between colloids and hydrophobized sand, which were not reflected by colloid breakthrough behavior. This was probably due to substantial energy barriers calculated for larger distances (∼27 to ∼75 nm, depending on ionic strength) between the solid matrix and colloids. It is concluded that the distinct surface roughness of sand grains and colloids probably weakened the strength of the short‐range attractive interactions, because larger amounts of surface area were still outside the effective distance for the short‐range interactions predicted by XDLVO. Regarding colloidal mobility, we concluded for our saturated porous systems that near‐surface attractive XDLVO interaction energies between OMCG colloids and hyrophobized sand did not significantly affect colloid mobility.